Narrative Review : Efek Samping Penggunaan Antibiotik Azitromycin Pada Pasien Covid-19 - Valentina Dian Suryani; Nera Umilia Purwanti; Nurmainah Nurmainah (Indonesian Journal of Pharmaceutical Education, 2023)
Corona virous is the cause of infection with Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). This disease was named by the World Health Organization, namely Coronavirus Disease 2019 or also known as COVID-19. In the management of COVID-19 patients using antibiotic therapy. Azithromycin is a broad-spectrum macrolide antibiotic that is the first line in the treatment of COVID- 19, because azithromycin has anti-inflammatory properties. The purpose of this study was to examine the side effects of using azithromycin as a treatment in COVID-19 patients based on a systematic review of various research articles that have been carried out. The method used is Literature review with SPIDER analysis. The results showed that azithromycin caused side effects in COVID-19 patients in the form of sudden cardiac death by triggering torsade de pointes and other ventricular arrhythmias. The conclusion is that azithromycin has been shown to cause the most side effects in COVID-19 patients.